Viscosities and Conductivities of [BMIM]Zn(Ac)xCly(x=0,1,2,3; y=3,2,1,0) Ionic Liquids at Different Temperatures - Hang Xu; Dandan Zhang (Journal of Chemistry)
Viscosity and conductivity data of BMIMZnAcxCly(x=0,1,2,3;  y=3,2,1,0) ionic liquids were detected at temperature ranging from 323.15 to 353.15 K with an interval of 5 K. The conductivities of different ionic liquids at the same temperature followed the trend [BMIM][ZnAcCl2] > [BMIM][ZnAc2Cl] > [BMIM][ZnCl3] > [BMIM][ZnAc3]. The viscosities of different ionic liquid abided by the order [BMIM][ZnCl3] > [BMIM][ZnAcCl2] > [BMIM][ZnAc2Cl] > [BMIM][ZnAc3]. Acetate ion could reduce the viscosity of ionic liquids. The relationship between viscosity/conductivity and temperature obeyed the Arrhenius equation and Vogel-Fulcher-Tammann (VFT) equation very well with above 0.99 correlation coefficients.